GAMBARAN KEPATUHAN HAND HYGIENE PADA PESERTA PROGRAM PENDIDIKAN DOKTER SPESIALIS DI RSUD ULIN BANJARMASIN - Qothrunnada, Salsabila; Rahmiati, Rahmiati; Mulyani, Nina; Wibowo, Agung Ary; Muthmainah, Noor (Homeostasis, 2023)
The account of Hospital Associated Infections (HAIs) remains high in Indonesia and worldwide. Cross-transmission can occur through contaminated healthworker hand, including residents. Hand hygiene is considered one of HAIs prevention control. This study sought to know hand hygiene compliance among Ulin Hospital’s residents based on gender and specialty. The observation was to checked on six steps standard procedure and five moments of hand hygiene. This observational descriptive study was conducted among internal medicine and surgery residents during October to November 2022. Samples were taken by consecutive sampling method. The result showed that hand hygiene compliance was 35%. Moreover, 38,1% residents adhered to 6 standard steps. Hand hygiene compliance between male 50% and female 20%; internal medicine 35% and surgery 34%. Compliance of each five moments hand hygiene was before aseptic 100%, after body fluid exposure 100%, before touching patient 38,1%, after touching patient 38,1%, and after touching patient surroundings 7,14%. Thus, the study concluded that male hand hygiene compliance was higher than female; internal medicine was higher than surgery. The highest compliance were before aseptic and after body fluid exposure. The present study emphasize the need for improving hand hygiene compliance among residents.